Survey of Traveler’s Diarrhea: Epidemiology and Testing Reveal the Source - Zhenguo Gao; Muti Mahe; Shabiremu Tuohetamu; Fang Li; Jian Zhang; Yidan Xia; Xiaona Sun; Abuzhalihan Naerkezi; Ruifang Huang; Hongbin Liu; Daxin Ni; Rong Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. To understand the causes and transmission routes of, as well as risk factors, for a Salmonella outbreak in a tour group. Method. A retrospective cohort design was used to conduct an epidemiological field investigation. Real-time fluorescent quantitative PCR, bacterial culture, and serological identification methods were used for pathogen detection and identification. Result. There were 7 cases of illness, and the attack rate was 46.67%. The onset date was concentrated on May 9 and 10. All cases were found in the tour group, and no cases occurred in the nontour group. The results of this retrospective cohort study showed that the consumption of boiled eggs for breakfast on May 9 was a common factor (R2 = 6.67, P=0.023). Salmonella enteritidis was identified from the patients’ stool and vomit. Conclusion. The food poisoning epidemic was caused by Salmonella enteritidis. In the summer and autumn, attention should be paid to preservation, processing, and cooking of food to avoid bacterial contamination. To prevent sickness, travelers should know the disease prevalence at their destinations in advance.